Modelo hidrodinâmico para análise de escoamento superficial em microdrenagem: uma contribuição à Geomorfologia Urbana - Souza, Luiz Humberto de Freitas (2024)
This thesis proposes a hydrodynamic model to analyze surface runoff in urban microdrainage, integrating elements of Geomorphology with a particular focus on the impacts of anthropogenic interventions on the landscape. The study aims to identify patterns of runoff concentration and flooding points in hypothetical precipitation scenarios, especially in urban roadways. The analysis concentrates on morphology, as well as the physical and topographic characteristics of the built environment that directly affect runoff, including slope, land use, and the roughness of surface materials. The modeling is processed using the PCSWMM software, which facilitates the two-dimensional simulation of DSR. For the organization and analysis of spatial data, the QGIS tool is employed. Methodologically, two urban scenarios were considered for simulating and studying the hydrological-hydraulic conditions of DSR in the area defined by the Santa Mônica Campus of the Federal University of Uberlândia/MG. This analysis encompasses the following situations: 1) Roadway layout and topography from the year 1989, as presented in the Institution's Physical Master Plan (DICIE-UFU, 1991); 2) Topographic survey conducted between 2013 and 2014. The hydrological conditions in both situations were defined by specifying design rainfall events with Return Periods (Tr) of 10 and 50 years. These values, according to Porto (1995) and SUDERHSA (2002), are parameters commonly used in drainage projects. The results obtained aim to enhance the understanding of runoff dynamics in urban environments, providing essential information for planning and implementing strategies for stormwater management. The integrated approach between Geomorphology and hydraulic-hydrological modeling, combined with the use of QGIS and PCSWMM software, seeks to broaden the discussion on the dynamic behavior of stormwater under similar conditions. The development of characteristic indicators alongside thematic mapping of areas prone to surface runoff concentration and flooding will serve as a reference for improving forecasting techniques and management of adverse natural events in urbanized areas.